SUBSTANCE USE DISORDERS AMONG EMERGING AND YOUNG ADULTS: AN EPIDEMIOLOGICAL STUDY - Qadeer, Rana A (My University, 2017)
Objectives: We investigated the prevalence of substance use disorders among emerging adults and quantified the extent to which emerging adults, compared to young adults, are at increased odds for substance use disorders. Methods: Data come from the 2012 Canadian Community Health Survey – Mental Health (CCHS-MH). Respondents were 15–39 years of age (n=9228) and were categorized as: early emerging adults (15-22 years); late emerging adults (23-29 years); and, young adults (30-39 years). Substance use disorders (alcohol or drug abuse/dependence) were measured using the Composite International Diagnostic Interview 3.0. The prevalence of substance use disorders was compared across age groups using design-based χ2 analyses. Odds ratios (OR) and 95% confidence intervals (CI) were computed from logistic regression models adjusting for sociodemographic and health covariates. All analyses were weighted to maintain representativeness of the study sample to the Canadian population. Results: The prevalence of alcohol use disorder was 8.0%, 6.6%, and 2.7% for early emerging adults, late emerging adults, and young adults respectively. For drug use disorder, the prevalence was 6.4%, 3.6%, and 1.3%. Compared to young adults, early and late emerging adults were more likely to report substance use disorders (p<0.01). The prevalence of drug use disorder was higher among early versus late emerging adults (χ2=119.8, p=0.01). Among all age groups, males were more likely to report alcohol or drug use disorders (p≤0.01 for all). After covariate adjustment, early and late emerging adults had greater odds of reporting alcohol (OR=3.2, 95% CI=2.2-4.9 and OR=2.4, 95% CI=1.6-3.4, respectively) or drug (OR=4.2, 95% CI=2.5-7.0 and OR=2.5, 95% CI=1.6-4.1, respectively) use disorders compared to young adults. Conclusion: Emerging adulthood represents an important developmental period in which individuals are at increased odds of reporting substance use disorders. This finding has implications for the provision of screening and treatment of substance use disorders as these individuals transition from the pediatric to adult healthcare system.
Keywords: alcohol use disorder; drug use disorder; emerging adults